Positioning estimation of undetected marker using Kalman filter for colored reference markers based image-guided surgery system - Elsamnah, Fahed; Sediono, Wahju; Al Jeroudi, Yazan (Kyushu University, Japan, 2017)
Image-guided surgery (IGS) is used in any surgical procedure where the optical image tracking, of the reference markers, indirectly guide the procedure. This paper proposed an optimal estimation algorithm to be used in image-guided surgery system to estimate the position of the undetected reference markers in space. Matlab simulation, using Kalman filter algorithm, on the proposed system showed an enhancement of the position accuracy of the colored reference markers less than 2.53mm root mean square error performance at the distance from 770 to 970 mm. The root mean square error of the three angles (α, θ, φ) was enhanced by less than 1.32 degree. Eventually, positioning estimation of undetected marker based on Kalman filter enhances the capabilities of image-guided surgery system.